Structural and cross-cultural validity of the Afrikaans for the Western Cape Disabilities of the Arm, Shoulder and Hand (DASH) questionnaire - Susan de Klerk; Christina Jerosch-Herold; Helen Buchanan; Lana van Niekerk (Journal of Patient-Reported Outcomes, 2023)
Abstract Background The Disabilities of the Arm, Shoulder and Hand (DASH) questionnaire has been translated and cross-culturally adapted to Afrikaans for the Western Cape, within the public health service context of South Africa. The aim of this study was to evaluate structural validity, internal consistency, and cross-cultural validity/measurement invariance of this new translation to increase applicability and clinical utility in a public health service context. Methods During this cross-sectional study, exploratory factor analysis (EFA) was conducted with parallel analysis and oblimin rotation. Confirmatory factor analysis (CFA) and multiple group confirmatory factor analysis (MGCFA) to assess cross-cultural validity/measurement invariance, was employed to test model fit with X 2 goodness-of-fit statistic, root mean square error of approximation (RMSEA), standardized root mean square residual (SRMR) and comparative fit index (CFI). Internal consistency was calculated using Cronbach’s alpha. Results 109 women and 110 men (n = 219) completed the Afrikaans for the Western Cape and the South African English DASH questionnaire, used during the analysis. Unidimensionality of the Afrikaans for the Western Cape DASH questionnaire was not supported in the 218 questionnaires eligible for inclusion in the analysis [X 2 (df) = 1799.10 (405); p value = < 0.01; RMSEA (90% CI) = 0.126 (0.120–0.132); SRMR = 0.09 and CFI = 0.984]. EFA revealed a two-factor structure with Eigenvalues exceeding one explaining 55% and 7% of the variance. The two-factor structure of the Afrikaans for the Western Cape DASH questionnaire was supported during CFA. Cronbach’s alpha revealed good internal consistency of both factors [factor 1 = 0.97 (0.96, 0.97) and factor 2 = 0.92 (0.90, 0.94)]. MGCFA conducted between 218 Afrikaans for the Western Cape DASH and 219 South African English DASH questionnaires (N = 437) revealed that the data supports configural, metric and scalar invariance models during initial model fit assessment. Subsequent hypotheses testing comparing the nested models revealed that scalar invariance holds. Conclusion The Afrikaans for the Western Cape DASH questionnaire revealed a two-factor structure with good internal consistency across the two factors and demonstrated measurement invariance with the South African English DASH questionnaire.